2010
DOI: 10.1590/s1517-83822010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of piperine for the control of aflatoxin intoxication in rats

Abstract: Aflatoxins are mycotoxins that have important toxic effects on human and animal health, even if consumed at low doses. The oral administration of piperine (1.12 mg/kg) during 23 days in rats seemingly interfered with the toxicity of aflatoxins, decreasing hepatic injuries and the leukocyte depletion in experimentally intoxicated animals.Key words: aflatoxins, piperine, experimental intoxication, rats. Piperine (1-piperol piperidine) is an amide found in Piper species that non-specifically increases the bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Cardoso et al (2009), while working with broiler chickens, found that orally administered piperine did not interfere on weight gain or liver relative weight. However, liver histopathological changes were observed in a dose-dependent manner, indicating that 1.12 mg kg -1 of piperine, with oral route of administration, is nontoxic for broiler chickens, as previously reported for rats and mice (Dogra et al, 2004;Gagini et al, 2010).…”
Section: Introductionsupporting
confidence: 79%
“…Cardoso et al (2009), while working with broiler chickens, found that orally administered piperine did not interfere on weight gain or liver relative weight. However, liver histopathological changes were observed in a dose-dependent manner, indicating that 1.12 mg kg -1 of piperine, with oral route of administration, is nontoxic for broiler chickens, as previously reported for rats and mice (Dogra et al, 2004;Gagini et al, 2010).…”
Section: Introductionsupporting
confidence: 79%
“…Some phytobiotics act as growth promoters and others can neutralize the toxic effects of xenobiotics like AFB 1 [43,49,50]. The covalent bonding of AFB 1 -epoxide with DNA modifies the structure of the nucleic acid and biological activity, generating RNA and DNA adducts with potential mutagenic, carcinogenic and teratogenic characteristics [51].…”
Section: Resultsmentioning
confidence: 99%
“…Aliquots of these solutions were prepared in the concentration of 0.5 mg·kg −1 body weight of chicken and administered daily by gavage, starting with a 10-day-old broiler. The methodology was adapted from Gagini et al [43]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further study investigated the toxic effects of piperine on the liver [144]. After the administration of 1.12 mg/kg b.w./day for 23 days, no histopathological lesions were observed.…”
Section: Toxicological Studiesmentioning
confidence: 99%